Dr. Francisco Valdés Lazo: an exceptional physician - Alida Paula Avila; Yenny Téllez Paula; Vilma Álvarez Benítez (Universidad de Ciencias Médicas de La Habana, 2021)
José Martí declared: "Knowing how to sacrifice is the price of lasting success at everything."  The work of Dr. Francisco Valdés Lazo can be summed up in great sacrifices and successes during all his working life.  He was an exceptional physician who knew how to link his administrative responsibilities to teaching and research. He was a tireless fighter for the advances in Medicine, the founder of the Cuban School of Pediatrics and a great example for Cuban and Latin American doctors. During his student life, he collaborated prominently with different activities, being the founder of the revolutionary militias. As soon as he graduated, he started to work in the pediatric hospital of Santa Clara. He also cared for the militiamen who were mobilized in the fight against bandits in El Escambray. After he finished his social service, he had already demonstrated his leadership condition; therefore, he was designed as deputy director of the Pedro Borrás Pediatric Hospital.  His qualities as revolutionary as well as his intelligence and total dedication to work allowed him to be promoted to different management positions until he was positioned at the central level.  He provided scientific advice to different countries in the world such as Guinea Bissau, Nicaragua, Bolivia, Mexico, and Guatemala.  He taught numerous national and international postgraduate courses and received different awards as physician and researcher. His humanism, management methods, affable character and his sense of humor, even in difficult situations, make this Cuban medical professional an example to be followed for all generations of doctors.